English Language Learning and Technology: Lectures on applied linguistics in the age of information and communication technology - Carol A. Chapelle (Language Learning & Language Teaching, 2003)
This book explores implications for applied linguistics of recent developments in technologies used in second language teaching and assessment, language analysis, and language use. Focusing primarily on English language learning, the book identifies significant areas of interplay between technology and applied linguistics, and it explores current perspectives on perennial questions such as how theory and research on second language acquisition can help to inform technology-based language learning practices, how the multifaceted learning accomplished through technology can be evaluated, and how theoretical perspectives can offer insight on data obtained from research on interaction with and through technology. The book illustrates how the interplay between technology and applied linguistics can amplify and expand applied linguists' understanding of fundamental issues in the field. Through discussion of computer-assisted approaches for investigating second language learning tasks and assessment, it illustrates how technology can be used as a tool for applied linguistics research.